The relationship between tourism, financial development and economic growth in India - Ramphul Ohlan (Future Business Journal, 2017)
This study investigates relationship between tourism and economic growth in India by considering the relative importance of financial development over the period of 1960-2014. The results of newly-developed Bayer and Hanck combined test indicate that tourism, economic growth and financial development are cointegrated. It is shown that the inbound tourism spurs economic growth in India both in long-run and short-run. In addition, the analysis indicates the presence of a long-run one-way Granger-causation running from tourism to economic growth. It is suggested that policies for attracting more international tourists should be promoted.
Keywords: 650; ARDL model; Bayer and Hanck model; Economic growth; India; Variance decomposition; VECM